2021
DOI: 10.3390/pharmacy9010054
|View full text |Cite
|
Sign up to set email alerts
|

What Do Young Adults Think about the Safety of Over-the-Counter Analgesics? Findings from a Cross-Sectional Survey

Abstract: Analgesics are commonly used over-the-counter (OTC) medicines readily available for purchase, sometimes without advice of a health professional. However, analgesics can cause harm even when taken according to dosing recommendations. Young adults may be more vulnerable to harm if they perceive low risk with OTC analgesic use, or struggle to interpret dosing instructions. This study aimed to explore factors affecting how young adults use OTC analgesics and associated perceptions of safety. An online survey was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 40 publications
(104 reference statements)
3
5
2
1
Order By: Relevance
“…Indeed, including pain nodes in the network revealed substantially stronger associations between OTCA usage and on-label symptoms than between OTCA and off-label symptoms (i.e., anxiety and depression). This is in line with previous research on OTCA usage among adolescents [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Indeed, including pain nodes in the network revealed substantially stronger associations between OTCA usage and on-label symptoms than between OTCA and off-label symptoms (i.e., anxiety and depression). This is in line with previous research on OTCA usage among adolescents [ 50 ].…”
Section: Discussionsupporting
confidence: 93%
“…A recent meta review identified several knowledge gaps and inconsistencies in findings regarding OTCA usage among children up to the age of 18 [ 54 ]. Adolescents in particular face an increased risk of unintentional misuse of OTCA [ 50 , 55 ]. While it is reassuring that the associations between OTCA usage and pain were markedly larger than the associations with anxiety and depression, there is a need for a deeper understanding of the factors that influence decision-making regarding OTCA usage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of painkiller use in our study was similar to the results obtained by Duyster et al, who surveyed such use among school-leavers and university students aged 17-25 years in Australia [5]. The vast majority of that study's participants took painkillers once a month or less than once a month.…”
Section: Discussionsupporting
confidence: 90%
“…Outro aspecto abordado no instrumento, refere-se ao autocuidado, conhecimentos e práticas de automedicação em estudantes universitários [9,21,22]. Os principais fatores que podem contribuir para o uso irracional de medicamentos envolvem autodiagnóstico incorreto, escolha equivocada da terapêutica, falha em reconhecer riscos farmacológicos especiais por outras comorbidades ou características do paciente, risco de ocorrência de efeitos adversos raros (porém graves) e falha em reconhecer ou autodiagnosticar contraindicações, interações medicamentosas, alertas de segurança ou precauções de uso [23][24][25].…”
Section: Discussão Dos Resultadosunclassified